A CONTENT ANALYSIS OF THE READING COMPREHENSION QUESTIONS IN THE TEXTBOOK ENDORSED BY THE GOVERNMENT - Aulia Azmi; Noor Aisyah (Intensive Journal, 2023)
Material is a component of teaching to create a successful teaching and learning process. The purpose of this study is to describe the content of reading material in “Bahasa Inggris” textbook which endorsed by the government, especially the cognitive levels of the questions that follow the reading texts. This study used the qualitative research design. Meanwhile, the qualitative data of the research were cognitive level of questions that followed the reading texts. The researcher also used content analysis which was as one of the techniques used in qualitative research to collect and analyze the data of the textbook. Moreover, the instruments for analyzing cognitive level of questions that followed the reading texts were a checklist proposed by Igbaria (2013) and a guide for deciding the level of the questions based on the cognitive domain of Bloom’s taxonomy. The result showed that cognitive levels of questions that followed the reading texts found that 125 questions (89.9%) which were categorized as lower order thinking skills. Meanwhile, there were 14 (10.07%) questions which were categorized as higher order thinking skills. Thus, the questions which were categorized as Lower-order Thinking Skills (LOTS) were more dominant in the textbook.